RICE-HUSK ASH-CARBIDE-WASTE STABILIZATION OF RECLAIMED ASPHALT PAVEMENT (Nigerian Journal of Technology, 2016)
This paper present results of the laboratory evaluation of the characteristics of carbide waste and rice husk ash stabilized reclaimed asphalt pavement waste with a view to determine its suitability for use as flexible pavement material. The mixtures were subjected to British Standard heavy compactive effort to determine the compaction characteristics, California bearing ratio, durability and water absorption. Test results showed that the maximum dry density increased while optimum moisture content decreased with carbide waste content and lower rice husk ash contents at any fixed reclaimed asphalt pavement content in the mixes. Optimum California bearing ratio values of 62.0 % (unsoaked) and 66.0 % (soaked for 24 hours) were recorded for 75% RAP + 25% CW mix, with minimum water absorption of 5.7 % and resistance to loss in strength of 84.1 %, hence the recommendation of the mixture for use as sub-base material in flexible pavement construction.  http://dx.doi.org/10.4314/njt.v35i3.1